Market reaction on earnings announcement information contents: Analysis from book-to-market - Nainggolan, Rexon (International Journal of Financial, Accounting, and Management, 2024)
Purpose: This study examines the market’s reaction to information content during earnings announcements from the viewpoint of changes in the book-to-market ratio. Research methodology: This study used a quantitative approach and an event study methodology as the primary measurement. It applies a market model based on Indonesia’s equity market daily stock returns to analyze the cumulative average abnormal returns in firms with upward/downward book-to-market value changes. Results: The findings reveal that stock prices in Indonesia's stock equity grew significantly above the firms' book values, indicating that investors pay more attention to expected future returns than the accounting value. This study also reveals that changes in book value may cause more significant changes in market value, following the direction of information content. The study found that the market is more sensitive to bad news than to good news and noted a significant relationship between book-to-market and post-earnings announcement abnormal returns. Limitations: This  study did not cover the long-term impact of the long-horizon test. A long-horizon test may provide evidence of market efficiency from the long-term perspective. Accordingly, this study suggests an issue for future research.   Contribution:  This study contributes to the literature by suggesting that testing market efficiency from the view of changes in book-to-market provides robust grounds to explain the market reaction to good or bad news information content. Novelty: Our findings show that Rp. One adjustment in book value in the Indonesian stock market corresponds to an average value of Rp. 16.43 adjustment in market value. This result implies that book value changes can lead to more significant changes in the market value.